Transformasi Kompetensi dan Profesionalisme Guru Pendidikan Agama Islam: Problematika dan Solusi untuk Meningkatkan Kualitas Pendidikan di Indonesia - Mukarromah, Mukarromah; Sartika, Rika (EL-BANAT: Jurnal Pemikiran dan Pendidikan Islam, 2024)
The professionalism of Islamic Religious Education (PAI) teachers in Indonesia faces significant challenges that affect the quality of teaching and learning. This study aims to identify key issues, including the lack of exemplary behavior among teachers, low professional competence, insufficient mastery of subject matter, suboptimal classroom management, limited use of technology, and a focus on cognitive-based evaluation. It also proposes comprehensive solutions, such as competency enhancement through training, expertise-based recruitment, and holistic evaluation covering cognitive, affective, and psychomotor domains. Employing a literature-based research approach, this study highlights strategic efforts to integrate value-driven and technology-based learning to meet the demands of modern education. The findings provide valuable insights for developing more effective Islamic education policies, ensuring improved teaching quality and better student outcomes.